Memories of my Anthropology professor - Dr. Manuel Zapata Olivella (The Voz a Vos Bulletin, 2021)
Memory as a student about his teacher of Anthropology in the Bachelor of Arts Education with an emphasis on Dance and Theater by the teacher Martha Jiménez at the Manuel Zapata Olivella Chair in March 2020.
Keywords: Memory; History; Zapata